Practical Review and Evaluation on Parenting Education - Jewish A. Merin (Institute of Advanced Engineering and Science, 2018)
Parenting Education aims to reinforce families and increase parenting practices. This study intended to evaluate the efficiency of the delivery of the Parenting Education Program and its effectiveness in attaining its program objectives tailored to address specific needs, organized parent-child activities, and helping parents to access community services and supports. The valuation of this is to assess the impact of the program on the family and child. The study utilized Asset Based Community Development (ABCD), for sustainable community-driven development, and builds on the assets that are already found in the community and mobilizes individuals, associations, and institutions to come together to build on their assets- not concentrate on their needs. The results revealed that the parenting education have a great charge to deliver program which is useful and effective. These pointed out to the conclusion that the program is grounded in research and evaluated with empirical studies best achieve the roles as the extension service of the agency.